2012
DOI: 10.1111/j.1447-0756.2011.01723.x
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of a pregnant unscarred uterus in an early secondary trimester: A case report and brief review

Abstract: Rupture of a pregnant uterus in early pregnancy and an unscarred uterus are extremely rare, and some non-specific symptoms might appear before this occurrence. We report the case of a multiparous woman (gravida 3, para 2) with uterine fundal rupture in her early second trimester (17+ weeks of gestational age), who presented upper abdominal discomfort and vomiting for 3 days, and progressed into sudden acute abdomen and shock. During emergent laparotomy, the entire amniotic sac was found in the peritoneal cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…Reported cases in the literature suggest underlying etiologies of abnormal placenta implantation [3][4][5][6][7][8][9] and congenital uterine abnormalities such as bicornuate uterus [10] and uterine septum [2]. Occasionally, no underlying cause is found [11][12][13]. The cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Reported cases in the literature suggest underlying etiologies of abnormal placenta implantation [3][4][5][6][7][8][9] and congenital uterine abnormalities such as bicornuate uterus [10] and uterine septum [2]. Occasionally, no underlying cause is found [11][12][13]. The cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…But if there is fundal rupture especially in early pregnancy, the diagnosis is often delayed due to non-specific symptoms and so other causes of acute abdomen should be ruled out. 5 This case highlights that curettage can also be a risk factor for spontaneous uterine rupture in early pregnancy. …”
Section: Discussionmentioning
confidence: 99%
“…4 Sun et al also reported similar case with fundal rupture at 17 weeks gestation in gravida 3. 5 Kharakwal et al reported rupture lateral wall of uterus at 20 weeks in G5P4. 6 As compared to our case, rupture uterus in these case reports were seen in higher birth order.…”
Section: Discussionmentioning
confidence: 99%